Computational Analysis Reveals a Successive Adaptation of Multiple Inositol Polyphosphate Phosphatase 1 in Higher Organisms through Evolution. (January 2014) - Kilaparty, Surya P.; Singh, Awantika; Baltosser, William H.; Ali, Nawab
Multiple inositol polyphosphate phosphatase 1 (Minpp1) in higher organisms dephosphorylates InsP6, the most abundant inositol phosphate. It also dephosphorylates less phosphorylated InsP5 and InsP4 and more phosphorylated InsP7 or InsP8 . Minpp1 is classified as a member of the histidine acid phosphatase super family of proteins with functional resemblance to phytases found in lower organisms. This study took a bioinformatics approach to explore the extent of evolutionary diversification in Minpp1 structure and function in order to understand its physiological relevance in higher organisms. The human Minpp1 amino acid (AA) sequence was BLAST searched against available national protein databases. Phylogenetic analysis revealed that Minpp1 was widely distributed from lower to higher organisms. Further, we have identified that there exist four isoforms of Minpp1. Multiple computational tools were used to identify key functional motifs and their conservation among various species. Analyses showed that certain motifs predominant in higher organisms were absent in lower organisms. Variation in AA sequences within motifs was also analyzed. We found that there is diversification of key motifs and thus their functions present in Minpp1 from lower organisms to higher organisms. Another interesting result of this analysis was the presence of a glucose-1-phosphate interaction site in Minpp1; the functional significance of which has yet to be determined experimentally. The overall findings of our study point to an evolutionary adaptability of Minpp1 functions from lower to higher life forms.